1984
DOI: 10.1115/1.3246765
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Drag for Two-Phase Flow Through High Permeability Porous Beds

Abstract: Pressure drop and void fraction measurements in two-phase (air–water) flow through porous beds of randomly packed spheres have been used to determine the interfacial gas–liquid drag and the gas–solid drag for the case of zero net liquid flux through the bed. The results, presented for beds of 3.18-, 6.35-, and 12.7-mm spheres, show that the interfacial gas–liquid drag term is of the same order as the gas-solid drag term when the particle size is greater than 6 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…It should be noted that this situation may correspond to creeping flows in low permeability media, although this remains controversial ( Rose, 20 0 0 ). However, in the case of high permeability media, such as the debris beds considered in this work, observations Tutu et al, 1983 ) have shown that coupling terms have a significant influence, even for the small Reynolds numbers, as recently pointed out by Chikhi et al (2016) . Therefore, the drag term in Eqs.…”
Section: Macroscopic Momentum Equations For Two-phase Flows In Poroussupporting
confidence: 65%
See 3 more Smart Citations
“…It should be noted that this situation may correspond to creeping flows in low permeability media, although this remains controversial ( Rose, 20 0 0 ). However, in the case of high permeability media, such as the debris beds considered in this work, observations Tutu et al, 1983 ) have shown that coupling terms have a significant influence, even for the small Reynolds numbers, as recently pointed out by Chikhi et al (2016) . Therefore, the drag term in Eqs.…”
Section: Macroscopic Momentum Equations For Two-phase Flows In Poroussupporting
confidence: 65%
“…As a consequence, very few data have been reported in the literature for flow in highly permeable media. The only relevant data (for inertial two-phase flows in particle beds) have been proposed by Tutu et al (1983) , and contain measurements of pressure drops, gas velocities and void fraction for zero-liquid rate only. Thus, pressure drop models have been validated either in non-representative conditions, for example from low velocity -viscous regime-experiments through sand as in Lipinski (1984) , or indirectly, from dryout heat flux experiments, as in Hu and Theofanous (1991) , by coupling the pressure drop model to heat exchange and mass transfer models.…”
Section: Macroscopic Momentum Equations For Two-phase Flows In Porousmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, only in relatively coarse packed beds and high-porosity matrices is this effect important. In connection with the packed beds, Tutu et al (1983), Saez 8.6 Microseopie Inertial Coefficient 447 and , Schulenberg and Müller (1987), and Tung and Dhir (1988) have examined these coefficients by using the experimental data for packed beds of spheres. No detail pore-level hydrodynamic analysis leading to the determination of these coefficients is presently available.…”
Section: Microscopic Inertial Coefficientmentioning
confidence: 99%